2015
DOI: 10.7547/8750-7315-105.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Syndesmotic Screw Design via Finite Element Analysis and Taguchi's Method

Abstract: Stress that occurs in syndesmotic screws is closely related to their geometry and dimensions. According to the results, a 3.5-mm cortical screw with the ideal screw design regarding optimal parameters to resist against stresses in the syndesmosis seems more reasonable to choose in syndesmotic fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Similarly, Er et al . developed an FE model of an ankle treated with four different types of syndesmotic screws 14. FE analyses were conducted to find the optimal combination of screw parameters using Taguchi’s robust design method 16.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Er et al . developed an FE model of an ankle treated with four different types of syndesmotic screws 14. FE analyses were conducted to find the optimal combination of screw parameters using Taguchi’s robust design method 16.…”
Section: Introductionmentioning
confidence: 99%
“…However, our calculations assumed a static case only. In cases of dynamic loading, some overloads that often exceeded the static ones several times could potentially occur [ 23 ]. The finite element modeling calculations showed that regular walking generates loads reaching peak values of 3.2 [ 24 ], landing from a jump from 2 to 12, and running even up to 13-times higher than the body weight [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It is worth mentioning that screws are one of the most important tools used in orthopedic surgeries like ankle joints surgery. 5 In most cases of ankle surgeries, screws are utilized individually or in a group to keep motionless and intact the injured bone throughout the treatment duration and so, reduction in the anatomical state. [6][7][8][9] The screws used in the syndesmosis impose restrictions on the movement of ankle joints.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been conducted as clinical trials on patients under treatment, tests on a specific cadaver and numerical modelling like finite element analysis to investigate stress distribution in screws and screw design. 5,8,9,[11][12][13][14][15][16][17][18][19] However, there is no reported work on considering the lifetime of screws and then, estimating the time for failure after the operation and before removing them (the second surgery).…”
Section: Introductionmentioning
confidence: 99%